1997
DOI: 10.1002/pro.5560061119
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel conserved sequence motif in flavoprotein hydroxylases with a putative dual function in FAD/NAD(P)H binding

Abstract: Abstract:A novel conserved sequence motif has been located among the flavoprotein hydroxylases. Based on the crystal structure and site-directed mutagenesis studies of p-hydroxybenzoate hydroxylase (PHBH) from Pseudomonas jluorescens, this amino acid fingerprint sequence is proposed to play a dual function in both FAD and NAD(P)H binding. In PHBH, the novel sequence motif (residues 153-166) includes strand A4 and the N-terminal part of helix H7. The conserved amino acids Asp 159, Gly 160, and Arg 166 are neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 50 publications
1
94
0
1
Order By: Relevance
“…3 and 4A), resulting in a tight protein-cofactor interaction. One-third of the protein-FAD contacts are strictly conserved among flavoprotein hydroxylases and cluster around the three fingerprint sequences (29).…”
Section: Resultsmentioning
confidence: 99%
“…3 and 4A), resulting in a tight protein-cofactor interaction. One-third of the protein-FAD contacts are strictly conserved among flavoprotein hydroxylases and cluster around the three fingerprint sequences (29).…”
Section: Resultsmentioning
confidence: 99%
“…WP_031302470.1, 60% identity), respectively. Multiple sequence alignment analyses revealed that HSPHZZ contained the conserved motif Gly-Ala-Glu-GlyAla (amino acids 166-170), which is associated with FAD-and NAD(P)H-binding [25] (Supplementary Figure S2). At the amino acid sequence level, HSPHZZ also showed high identity to p-nitrophenol monooxygenases from Acidovorax sp.…”
Section: Gene Cloning and Sequence Analysis Of Hsphzzmentioning
confidence: 99%
“…Notably, in renalase the isoalloxazine N5 position is solvent exposed [20]. In addition to the Rossman fold GXGXXG signature, flavoprotein hydroxylases display two highly conserved consensus sequences: the 'GD' and the 'DG' motifs [54]. Whereas, the former polypeptide region participates in FAD binding and is conserved in renalase, the latter motif, critical for the interaction with the nicotinamide nucleotide, is absent.…”
Section: Nadph-dependent Diaphorase Reactions With Various Artificialmentioning
confidence: 99%
“…Whereas, the former polypeptide region participates in FAD binding and is conserved in renalase, the latter motif, critical for the interaction with the nicotinamide nucleotide, is absent. In particular, Gly160 and His162 of PHBH, which are very important for NADPH binding [54], in renalase are both replaced by Pro residues (Pro162 and Pro164), excluding the presence of a functional NAD(P)-binding site in this protein. These considerations, combined with the observation that the FAD structural environment is incompatible with the required chemistry (confirmed by the production of superoxide upon reaction with O 2 [33] instead of hydrogen peroxide as typical in hydroxylases [52]), led to the logical conclusion that renalase cannot be a monooxygenase.…”
Section: Nadph-dependent Diaphorase Reactions With Various Artificialmentioning
confidence: 99%